Website-Based School Exam Information System (Case Study: SMA Negeri 1 Torue) - Eliasta Ketaren; Eric Alfonsius; Riski Risandi (Journal of Artificial Intelligence and Technology Information (JAITI), 2023)
A website-based school exam information system is an application that can process student exam data at SMA Negeri I Torue. The purpose of this research is to build a CBT (Computer Based Test) information system. This system can make it easier for research parties in terms of carrying out exams so that they become even more effective. This research in its application uses existing research methods such as data collection techniques used are observation and documentation methods as well as testing methods used descriptive testing methods using a Likert scale. The results of this study resulted in a test of 91.6% which can be categorized as very feasible.